2017
DOI: 10.1021/acs.chemmater.7b00506
|View full text |Cite
|
Sign up to set email alerts
|

Spirothiopyran-Based Reversibly Saturable Photoresist

Abstract: Super-resolution lithography holds the promise of achieving three-dimensional (3D) nanopatterning at deep subwavelength resolutions with high throughput. 3D super-resolution lithography schemes demonstrated thus far have all been serial in nature, primarily due to the lack of a photoresist chemistry that not only couples a saturable reversibly switchable reaction with a writing step but also has a low saturation threshold. Here, we demonstrate that combining the reversible photoisomerization of spirothiopyran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 38 publications
0
31
1
Order By: Relevance
“…To the best of our knowledge, ligation reactions of DASA photoswitches have not been reported so far and the reactivity as well as selectivity of this molecule class remain unknown. Selectively gated reactions are uncommon, with only a few successful systems known . The ability of molecules to react selectively in only one of its isomeric states is promising for the development of advanced materials, for example, for the use as inks in direct laser writing .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, ligation reactions of DASA photoswitches have not been reported so far and the reactivity as well as selectivity of this molecule class remain unknown. Selectively gated reactions are uncommon, with only a few successful systems known . The ability of molecules to react selectively in only one of its isomeric states is promising for the development of advanced materials, for example, for the use as inks in direct laser writing .…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24] The ability of molecules to react selectively in only one of its isomeric states is promising for the development of advanced materials, fore xample, for the use as inks in direct laser writing. Selectively gated reactions are uncommon, with only af ew successful systems known.…”
mentioning
confidence: 99%
“…[104,105] Kinetic measurements combined with photokinetic simulations showed that interference lithography using conventional light sources (e.g., a green laser) on a spirothiopyran maleimide-based system delivered high-resolution features (≈45 nm lines) in thick films (tens of µm) over large areas (hundreds of µm). [106] UV-vis irradiation of some azobenzene or spiropyran-based systems induced phase transitions from solid to liquid even at temperatures close to physiological ones. [107][108][109][110][111][112][113] We should also note that photoisomerization of the spiropyran system brings the dipole moment change Δμ = 8-15 D, [104] which makes it perfect candidate for the aqueous-based photoresist.…”
Section: Optical and Deep And Extreme Ultraviolet (Duv/euv) Lithographymentioning
confidence: 99%
“…[ 104,105 ] Kinetic measurements combined with photokinetic simulations showed that interference lithography using conventional light sources (e.g., a green laser) on a spirothiopyran maleimide‐based system delivered high‐resolution features (≈45 nm lines) in thick films (tens of µm) over large areas (hundreds of µm). [ 106 ] UV–vis irradiation of some azobenzene or spiropyran‐based systems induced phase transitions from solid to liquid even at temperatures close to physiological ones. [ 107–113 ]…”
Section: Patterning Approachesmentioning
confidence: 99%
“…UV irradiation triggers the photoconversion of the SP to MC isomer, whereas green light (the "depletion" wavelength) causes the ring-closing photoisomerization of MC back to the SP form. 28 Due to the presence of a thiolate anion in the MC form, this isomer selectively and irreversibly undergoes a thiol Michael addition reaction with maleimides, to give the Michael addition product (MAP). Overall, the transformation is described as:…”
Section: Introductionmentioning
confidence: 99%